1998
DOI: 10.1152/ajpregu.1998.274.4.r1050
|View full text |Cite
|
Sign up to set email alerts
|

A prostaglandin, not NO, mediates endothelium-dependent dilation in ventral aorta of shark (Squalus acanthias)

Abstract: In mammals, the vascular endothelium releases a variety of paracrine factors, including the vasodilatory prostaglandin (PG)I2 and nitric oxide (NO), which is generally accepted as the major endothelium-derived relaxing factor (EDRF) in mammals. Current evidence for the vascular NO-EDRF system in fishes is contradictory. In addition, the role of PGs in the control of fish vascular tension is also unclear. We have utilized isolated rings of the ventral aorta of the spiny dogfish shark to examine the ability of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 35 publications
3
33
0
Order By: Relevance
“…Higher vasoconstriction to acetylcholine was observed in ABA and EBA in I. conceptionis in comparison with G. laevifrons, and a minor effect of blockade with indomethacine in the maximum response to acetylcholine was observed in ABA and DA vessels in I. conceptionis as compared to G. laevifrons. In general, the results obtained in both of these species are partially in agreement with previous studies performed in species of great phylogenetic distance (agnathes, elasmobranches, teleost), that showed that acetylcholine induced contraction (Small et al, 1990;Miller and Vanhoutte, 1992;Evans and Gunderson, 1998a). However, the Ach-mediated vasoconstriction described in our study suggests that the coupled Ach-COX contraction produced when there is a decreased availability of nitric oxide (NO) is similar to that reported in human hypertension or hypertension models in rats (Vanhoutte et al, 2005;Shi et al, 2008).…”
Section: Introductionsupporting
confidence: 91%
“…Higher vasoconstriction to acetylcholine was observed in ABA and EBA in I. conceptionis in comparison with G. laevifrons, and a minor effect of blockade with indomethacine in the maximum response to acetylcholine was observed in ABA and DA vessels in I. conceptionis as compared to G. laevifrons. In general, the results obtained in both of these species are partially in agreement with previous studies performed in species of great phylogenetic distance (agnathes, elasmobranches, teleost), that showed that acetylcholine induced contraction (Small et al, 1990;Miller and Vanhoutte, 1992;Evans and Gunderson, 1998a). However, the Ach-mediated vasoconstriction described in our study suggests that the coupled Ach-COX contraction produced when there is a decreased availability of nitric oxide (NO) is similar to that reported in human hypertension or hypertension models in rats (Vanhoutte et al, 2005;Shi et al, 2008).…”
Section: Introductionsupporting
confidence: 91%
“…In fish, Ach induced contraction in all the species studied so far (Small et al, 1990;Olson and Villa, 1991;Miller and Vanhoutte,1992; Evans and Gunderson, 1998a). This contractile response was found even in the presence or absence of endothelium (Miller and Vanhoutte, 1986, 1992Olson and Villa, 1991;Evans and Gunderson, 1998b). Furthermore, a pharmacological study conducted in sharks found the presence of functional muscarinic receptors type 1 and 3, and non functional muscarinic receptors types 2 and 4 (Evans and Gunderson, 1998a).…”
Section: Vascular Response To Acetylcholinementioning
confidence: 88%
“…Unfortunately, we did not study specific inhibitors of COX or with endothelium denudate in order to corroborate the participation of endothelium in this response. By contrast, in shark (Squalus acanthias) or trout, it has been shown that an endothelium-dependent dilation in the presence of a calcium -ionophore (A-23187) promoted dilation by a prostaglandin and not by NO (Evans and Gunderson, 1998b;Olson and Villa, 1991;Miller and Vanhoutte, 2000) suggesting the presence of dilation mediated by prostanoids (Evans and Gunderson, 1998b;Miller and Vanhoutte, 2000).…”
Section: Acetylcholine-cyclooxygenases Vasoconstriction Pathwaymentioning
confidence: 99%
“…This was the first study in fish to suggest that NO stimulates the production of cGMP, and elicits a subsequent vasoconstriction. In addition, a vasoconstrictory effect of NO has been shown in the dogfish shark Squalus acanthias (Evans and Gunderson, 1998;Evans, 2000). Interestingly, a vasoconstriction mediated by cGMP signalling has recently been demonstrated in murine splenic vessels (Andrews and Kaufman, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Nitric oxide control of eel blood vessels endothelium (Nilsson and Söderström, 1997;Mustafa et al, 1997;Mustafa and Agnisola, 1998). Furthermore, it has been demonstrated that elasmobranchs lack a NO system and instead it is proposed that prostaglandins are the endotheliumdependent vasodilators in this group (Evans and Gunderson, 1998;Evans, 2000). NADPH diaphorase histochemistry and immunohistochemistry are two anatomical techniques that have been used previously to identify eNOS in the vasculature of mammals (Beesley, 1995).…”
Section: Discussionmentioning
confidence: 99%